The Uniqueness Heroines Depicted In Gillian Flynn’s Novels Entitled Gone Girl And Dark Places - Siti Alifah Tamir; Diah Tyahaya Iman (Vivid: Journal of Language and Literature, 2019)
This article is aimed to study the uniqueness of female character or heroine in Gillian Flynn’s novels entitled Dark Places (2009) dan Gone Girl (2012). The concept of heroin and gynocriticism approaches is used to examine the uniqueness of the main character in both novels. Amy Dunne in Gone Girl and Libby Day pada Dark Places can be considered as antiheroine. From the result of the analysis, it can be concluded that Flynn introduced an interesting female characterization.  The anti-heroine characters are portrayed in an intriguing plot.  She presents woman as offender and sexual manipulation interestingly. The exploration of feminine vulnerability to undermine the dominancy of masculine privilege has brought the themes of both novels to.